2000
DOI: 10.2500/108854100778248971
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Rhinitis: Epidemiology and Natural History

Abstract: Establishing a reliable estimate of the prevalence of allergic rhinitis is difficult; prevalence estimates range from as low as 4% to more than 40%. Epidemiology studies suggest the prevalence of allergic rhinitis in the United States and around the world is increasing. The cause of this increase is unknown; however, contributing factors may include higher concentrations of airborne pollution, rising dust mite populations, less ventilation in homes and offices, dietary factors, and the trend toward more sedent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 4 publications
3
65
0
2
Order By: Relevance
“…The prevalence of allergic conditions among controls in this study was similar to values reported in population-based U.S. studies, 23 with the exception of asthma, for which we observed a higher relative frequency. 24 -26 However, risk estimates associated with asthma were similar to those derived from other populations with lower reported prevalence.…”
Section: Discussionsupporting
confidence: 76%
“…The prevalence of allergic conditions among controls in this study was similar to values reported in population-based U.S. studies, 23 with the exception of asthma, for which we observed a higher relative frequency. 24 -26 However, risk estimates associated with asthma were similar to those derived from other populations with lower reported prevalence.…”
Section: Discussionsupporting
confidence: 76%
“…Strong evidence from a study in Denmark and a study in Japan showed that the prevalence of allergic rhinitis had increased significantly (Linneberg et al, 1999: Shida et al, 2000. The prevalence estimates of allergic rhinitis around the world ranged from 4% to more than 40% (Schoenwetter, 2000). Allergic rhinitis was estimated to affect at least 14% of Americans .…”
Section: Prevalence Of Allergic Rhinitismentioning
confidence: 99%
“…Allergic rhinitis is associated with fatal diseases such as asthma. The prevalence of allergic rhinitis around the world ranges from 4% to more than 40% (Schoenwetter, 2000). It is estimated that the prevalence of allergic rhinitis in Thailand is 20% of population (Pumhirun, Towiwat, & Mahakit, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…[8]. Он зарегистрирован у 86% пациентов с диагностированной бронхиальной астмой [9]. Привычную классификацию, разделяющую АР на сезонный и кругло-годичный, в последние годы по рекомендациям програм-мы ВОЗ ARIA рекомендуют дополнять выделением интер-миттирующей и персистирующей формы по продолжи-тельности клинических проявлений [10].…”
unclassified